2022
DOI: 10.1002/jsfa.11784
|View full text |Cite
|
Sign up to set email alerts
|

Gamma‐ray irradiation and microbiota transplantation to separate the effects of chemical and microbial diurnal variations on the fermentation characteristics and bacterial community of Napier grass silage

Abstract: BACKGROUND To investigate the contributions of chemical and microbial diurnal variations in fermentation characteristics and bacterial community of Napier grass silage, gamma‐ray irradiated Napier grass harvested at 07.00 h (AM), 12.00 h (M) and 17.00 h (PM) was inoculated with the microbiota derived from Napier grass harvested at AM, M and PM in a 3 (irradiated forage: AMG, MG and PMG) × 3 (microbiota: AMM, MM and PMM) design and then ensiled for 14 and 60 days. RESULTS Napier grass harvested at various times… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Ensiling is a well-established and low-cost method for preserving fresh forage with high biological potential ( Pakarinen et al, 2011 ). In the natural ensiling process, the epiphytic bacteria converting water soluble carbohydrates (WSC) in forage under anaerobic conditions, thereby producing organic acids (mainly lactic acid), which creates an acid environment to inhibits undesirable microorganisms ( Dong et al, 2022 ), allowing the nutritional properties of forage to be preserved for a long time, this acidification inhibits the growth of spoilage microorganisms ( Xu et al, 2017 ), thus allowing for long-term preservation of forage nutritional characteristics. Silage has become increasingly important worldwide due to its resilience against climatic variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensiling is a well-established and low-cost method for preserving fresh forage with high biological potential ( Pakarinen et al, 2011 ). In the natural ensiling process, the epiphytic bacteria converting water soluble carbohydrates (WSC) in forage under anaerobic conditions, thereby producing organic acids (mainly lactic acid), which creates an acid environment to inhibits undesirable microorganisms ( Dong et al, 2022 ), allowing the nutritional properties of forage to be preserved for a long time, this acidification inhibits the growth of spoilage microorganisms ( Xu et al, 2017 ), thus allowing for long-term preservation of forage nutritional characteristics. Silage has become increasingly important worldwide due to its resilience against climatic variations.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to explore the dynamic changes occurring in the epiphytic microbiota source during ensiling ( Xu et al, 2017 ). The composition of epiphytic microbiota source on fresh forage surface is highly heterogenous ( Dong et al, 2022 ), being primarily composed of LAB, yeasts, and molds, and it varies considerably among different types of forage. The contribution of the epiphytic microbiota source to silage fermentation quality also varies.…”
Section: Introductionmentioning
confidence: 99%
“…However, possible effects brought by these diurnal changes on silage fermentation are rarely explored, likely because those effects are difficult to differentiate from the effects brought by chemical changes. Recently, silage researchers started to use microbiota transplantation to clarify the role of exogenous epiphytic microbiota in silage quality ( 2 , 6 ). They demonstrated that exogenous microbiota can reconstruct a similar function in the recipient plant.…”
Section: Introductionmentioning
confidence: 99%
“…Ensiling is a process for epiphytic lactic acid bacteria (LAB) to use water-soluble carbohydrates (WSC) in forage to produce lactic acid [ 4 ]. This process lowers the pH of the silage and inhibits the growth of undesirable microorganisms [ 5 ].…”
Section: Introductionmentioning
confidence: 99%